Intra-arterial Thrombolysis in Second Trimester of Pregnancy. A Case Report - Pongrácz, Endre (J Crit Care Med (Targu Mures), 2015)
Here we present a successful intra-arterial thrombolysis performed in the second trimester of pregnancy (21 weeks). The intervention resulted in complete recanalization of the occluded right middle cerebral artery and favourable clinical and gestational outcome. Together with cases described in respective medical literature our report affirms that in pregnancy acute ischemic stroke could be treated effectively applying intra-arterial thrombolysis (using rt-PA). This therapy could provide opportunity to help in such desperate situations.